Measuring the differences of neighbourhood environment and physical activity in gated and non-gated neighbourhoods in Karachi, Pakistan - Gul, Yasmeen; Zahid, Sultan; Moeinaddini, Mehdi; Jokhio, Gul A. (Taylor & Francis, 2018)
Neighbourhood environment (NE) is important for physical activity (PA); however, no studies have compared the NE and PA in gated neighbourhoods, especially in developing countries. Therefore, the objective of this study is to compare NE and PA between gated and non-gated neighbourhoods. Objective and subjective (n = 1042) methods and independent sample t-tests were used. Results show that all the indicators are significantly different except housing density. Vigorous Physical Activity (VPA) is higher in gated but walking is higher in non-gated neighbourhoods. Therefore, it can be concluded that gating can reduce walking habits of people living in gated neighbourhoods in developing countries.